International experience in determining the cost-effectiveness thresholds - T. P. Bezdenezhnykh; N. Z. Musina; V. K. Fedyaeva; T. S. Tepcova; V. A. Lemeshko; V. V. Omelyanovsky (Фармакоэкономика, 2019)
The article reviews international methodological guidelines, regulatory documents and existing approaches to the determination of the costeffectiveness threshold (CeT), also known as the willingness-to-pay threshold (WTP), the threshold value of the incremental cost-effectiveness ratio (ICeR), in europe (england and Wales, Scotland, Ireland, France, Belgium, Denmark, the netherlands, Germany, Sweden, Finland, norway, Poland), America (the USA, Canada, Brazil), Asia (Japan, South korea, Taiwan, Thailand), in Australia and new Zealand. The CeT is commonly used to rationalize decision-making in health cost reimbursement. The present review demonstrates that just a few countries (englandandWales,Thailand,Poland,USA) have introduced the explicit value of CeT into their decision making. Some countries (Australia,Canada,new Zealand, thenetherlands,Sweden, andBrazil) use CeT in an implicit manner implying that no specific CeT value is defined by law. In other countries (Finland,Sweden,norway,France,Germany,Denmark,Japan,South korea,Taiwan), the role of the threshold in health reimbursement remains uncertain despite the presence of HTA systems. The CeT is expressed as additional cost per unit of incremental health benefit, which is represented by quality-adjusted life year (QALY) in most counties. However,PolandandBrazilallow using life years gained (LYG) as a measure of additional benefit neglecting the quality of life. In thenetherlandsandengland, different CeT values are applied to the health technology under assessment depending on the severity or rareness of the disease and some other factors.